1995
DOI: 10.1037/0097-7403.21.3.218
|View full text |Cite
|
Sign up to set email alerts
|

A postsample cue to forget does initiate an active forgetting process in pigeons.

Abstract: Remember (R)-and forget (F)-cued training trials differed in whether the sample stimulus was or was not relevant to predicting trial outcome. Delayed matching-to-sample (DMTS) accuracy was lower on trials in which the F, rather than the R, cue followed sample presentation (F-cue effect). Because both types of training trials involved the same probability of end-of-trial reinforcement and pattern of discriminated test responding, the F-cue effect could not result from the F cue triggering negative affect, indis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In addition, a one-sample t -test evaluated against 50% indicated that performance on forget-probe trials was not significantly different from chance, t (3) = 1.00, p = 0.39. The chance levels of performance on forget-probe trials indicates that the forget cue is indeed directing the subject to forget the sample stimulus, a finding in line with other studies using the directed forgetting paradigm [32,33]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, a one-sample t -test evaluated against 50% indicated that performance on forget-probe trials was not significantly different from chance, t (3) = 1.00, p = 0.39. The chance levels of performance on forget-probe trials indicates that the forget cue is indeed directing the subject to forget the sample stimulus, a finding in line with other studies using the directed forgetting paradigm [32,33]. …”
Section: Resultssupporting
confidence: 88%
“…On the basis of behavioural/lesion [27,28], neurochemical [29], and anatomical [30,31] studies, the NCL is considered, much like the PFC for mammals, to be the main integrative and executive area of the avian brain. The pigeons were trained on a directed forgetting [32,33] version of the delayed matching-to-sample task, a standard test of working memory used across a number of species, including birds, rats, monkeys, and humans. The birds were first shown a sample stimulus and then presented with either a remember cue or a forget cue (Figure 1A and 1B; see Materials and Methods).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these indirect means are interesting to pursue, but they do not provide us with definitive answers. The key for future studies is to find ways to present free rewards yet at the same time ensure that the forget cue functions in its intended role [12].…”
Section: Future Directionsmentioning
confidence: 99%
“…When alternative rewarded tests follow F cues in substitution procedures, the interpretation of results may depend on the nature of the substituted task and the required response (Grant & Barnet, 1991; Kendrick et al, 1981). In some designs (e.g., Grant & Barnet, 1991; Grant & Soldat, 1995), a random stimulus was presented at test after F cues and choices were rewarded indiscriminately. This may train subjects to respond non-differentially after seeing an F cue, resulting in the performance discrepancy between regular R-cued trials and F-cued probes.…”
mentioning
confidence: 99%